Gamification Based On Blockchain Technology To Enhance Student Centered Learning - Qurotul Aini; Ninda Lutfiani; Muhammad Suzaki Zahran (Universitas Raharja, 2021)
Gamification, the application of mechanical game techniques in non-game contexts, has become the primary choice underlies current education. Educational gamification can provide solutions to problems that arise due to traditional learning methods considered less under current human behavior. Blockchain has become a hot topic of discussion that is overgrowing in recent years. Blockchain comes from a world community and company that acts as infrastructure technology that develops in various fields, both industry and education. The main advantage of blockchain is that it is free from third parties so that the security, transparency, and integrity of the blockchain is quite high. At present, research on the blockchain that implemented in the field of educational gamification is still minimal in number. Our paper will identify and discuss the main problems related to education by implementing educational gamification applied to the Blockchain system. This paper proposes an initial gamification model as a foundation for the development of future applications and research.